The Role of Women's Creativity in the Development of Kuwaiti Short Story Writing - Sanjar Dusmatov (Academia One Publishing, 2025)
This article explores the role of women's creativity in the development of Kuwaiti short story writing. It examines in detail how the emergence of women's literature in the Persian Gulf countries, particularly Kuwait, is linked to the advancement of women's education. The article analyzes the themes of women's works, with a special focus on the problems of women in family and society, as well as social reforms. It highlights the shift from a romantic portrayal of heroines struggling with traditions but remaining helpless, to the emergence of a new Kuwaiti woman who is aware of herself as an individual and capable of fighting for her independence. The article also discusses the evolution of Kuwaiti short story writing from traditional plots to complex artistic techniques borrowed from world literature, which contributed to the enrichment of artistic language and the improvement of form
Keywords: woman writer; literature; Persian Gulf